The Impact of TikTok Use on Memorization Skills in Early Childhood from a Risk and Benefit Analysis Perspective - Rahmat Dani Diantoro (CV. Megantara Abdi Nusa, 2025)
TikTok has become one of the most popular digital platforms among children, offering access to various types of content, including educational materials that can support memorization skills. Early childhood, defined as the developmental stage from ages 0 to 6, is a critical period during which appropriate stimulation can enhance cognitive abilities, particularly memory retention. This study aims to analyze the impact of TikTok use on improving memorization skills in early childhood from both risk and benefit perspectives. Using a qualitative approach with a literature review method, the research examines previous studies related to the role of TikTok and other audiovisual digital media in young children's learning processes. The findings indicate that TikTok can provide several benefits, such as enhancing memory retention, facilitating access to learning materials, increasing learning motivation, and introducing new vocabulary. However, it also presents risks, including potential overdependence, reduced social interaction with the immediate environment, and exposure to inappropriate content without parental supervision.